The Role of The Appreciation of History Education, the Internalization of Pancasila Ideology and Religious Values on Creating the Nationalism Attitude - Na’im, Mohamad (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2012)
The purpose of this Research is to review the contribution level and the significance of the appreciation of history education, the internalization of Pancasila ideology and the internalization of religious values on creating the nationalism attitude. This research uses two approaches, which are quantitative and qualitative with concurrent embedded strategy. The primary in this research design is quantitative and qualitative as the secondary. The result of this research indicates the appreciation of history education, the internalization of Pancasila and the internalization of religious values. The importance of these roles can be discovered from 78.2% of contribution coefficient. The appreciation of history education contributes 27.84%, the internalization of Pancasila produces 14.39%, and the internalization of religious values brings 35.97%. The role of religious values on the appreciation of the building of nationalism attitude has a huge impact, bigger than the appreciation of history education and the internalization of Pancasila. Those three variables have role in the building of nationalism attitude which utilize as input material, that improving the student’s nationalism attitude can be conducted by enhancing the appreciation of history education, the internalization of Pancasila and the internalization of religious values about the life of society, nationhood, and statehood.